Anti-inflammatory activity of medicinal plants: A review - Sandeep Sahu, Sandeep Sahu; Amrita Chourasia, Amrita Chourasia (International Journal of Indigenous Herbs and Drugs, 2018)
Medicinal plants continue to be of interest for several reasons including lack of availability of a satisfactory therapy of several clinical conditions inflammatory disorders being one of them. Inflammation is a defensive response that is characterized by redness, pain, heat, and swelling and loss of function in the injured area. Inflammation is body’s nonspecific internal systems of defense, the response of a tissue to an accidental cut is similar to the response that results from other types of tissue damage, caused by burns due to heat, radiation, bacterial or viral invasion. Anti-inflammatory drugs like NSAIDs used to reduce the swelling and pain of inflammation. Long-term uses of NSAID cause adverse side effects and damage human biological system such as liver, gastrointestinal tract etc. The management of inflammation related diseases is a real issue in the rural community; the population in these areas uses many alternative drugs such as substances produced from medicinal plants. Herbal products from medicinal plants are playing a major role to cure many diseases associated with the inflammation. Many conventional drugs are available in the market to treat the inflammation which produces various side-effects. Due to these side-effects there is need for the search of newer drugs with less or no side-effects. In this review an attempt has been made to investigate the anti-inflammatory activity of some medicinal plants. It can be helpful to researchers in the study of anti-inflammatory substances from plants. This also may serve as a guide for pharmacologists studying the mechanisms of action and anti-inflammatory effects of these substances.